2012
DOI: 10.1126/science.1223447
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Absorption Enhancements Due to the Mixing State of Atmospheric Black Carbon

Abstract: Atmospheric black carbon (BC) warms Earth's climate, and its reduction has been targeted for near-term climate change mitigation. Models that include forcing by BC assume internal mixing with non-BC aerosol components that enhance BC absorption, often by a factor of ~2; such model estimates have yet to be clearly validated through atmospheric observations. Here, direct in situ measurements of BC absorption enhancements (E(abs)) and mixing state are reported for two California regions. The observed E(abs) is sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

54
683
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 668 publications
(747 citation statements)
references
References 25 publications
54
683
10
Order By: Relevance
“…were about 5-7 h in the afternoon given that the rate constant between OH radicals and NO x for HNO 3 formation (k rxn ) is equal to 7.9 × 10 −12 cm 3 molecules −1 s −1 (Brown et al, 1999;Cappa et al, 2012). Such estimation further supports our hypothesis that OOA-1 and OOA-2 were fresh SOA produced in the local atmosphere.…”
Section: Chemical Characteristics Of Oa As a Function Ofsupporting
confidence: 72%
See 3 more Smart Citations
“…were about 5-7 h in the afternoon given that the rate constant between OH radicals and NO x for HNO 3 formation (k rxn ) is equal to 7.9 × 10 −12 cm 3 molecules −1 s −1 (Brown et al, 1999;Cappa et al, 2012). Such estimation further supports our hypothesis that OOA-1 and OOA-2 were fresh SOA produced in the local atmosphere.…”
Section: Chemical Characteristics Of Oa As a Function Ofsupporting
confidence: 72%
“…A complex mixture of gas-phase organic compounds with a wide range of volatilities and molecular structures are co-emitted with BC from vehicles, contributing prominently to the urban SOA burden (Gentner et al, 2017, and references therein). Although it is not straightforward to identify the role of individual SOA precursors, previous studies have shown that organic coating thickness of BC particles and their degree of oxygenation increased with photochemical age or oxidant levels in the atmosphere (Cappa et al, 2012;Liu et al, 2015;Wang et al, 2017). Of particular concern is the timescale that is required for sufficient SOA condensation to modify the physical, chemical, and optical properties of BC near emission sources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While freshly emitted EC may contain limited coating, atmospheric aging such as coagulation with other particles, condensation of vapors, and in-cloud processing could cause EC to internally mix with other chemical species (e.g., Moffet and Prather, 2009). Cappa et al (2012) and Lan et al (2013) had observed a limited enhancement due to the mixing state of ambient EC, however, other studies confirmed the enhancement effect of internally mixing under various conditions (Wei et al, 2013;Zhang et al, 2008). The internally mixing can result in enhanced absorption by nearly 2-fold and scattering capacity by approximately 10-fold at 80% relative humidity (RH) relative to fresh particles (Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 91%